Adaptation to a low carbohydrate high fat diet is rapid but impairs endurance exercise metabolism and performance despite enhanced glycogen availability. (19th August 2020) - Burke, Louise M.; Whitfield, Jamie; Heikura, Ida A.; Ross, Megan L. R.; Tee, Nicolin; Forbes, Sara F.; Hall, Rebecca; McKay, Alannah K. A.; Wallett, Alice M.; Sharma, Avish P.
Abstract : Key points: Brief (5–6 days) adaptation to a low carbohydrate high fat diet in elite athletes increased exercise fat oxidation to rates previously observed with medium (3–4 weeks) or chronic (>12 months) adherence to this diet, with metabolic changes being washed out in a similar time frame. Increased fat utilisation during exercise was associated with a 5–8% increase in oxygen cost at speeds related to Olympic Programme races. Acute restoration of endogenous carbohydrate (CHO) availability (24 h high CHO diet, pre‐race CHO) only partially restored substrate utilisation during a race warm‐up. Fat oxidation continued to be elevated above baseline values although it was lower than achieved by 5–6 days' keto adaptation; CHO oxidation only reached 61% and 78% of values previously seen at exercise intensities related to race events. Acute restoration of CHO availability failed to overturn the impairment of high‐intensity endurance performance previously associated with low carbohydrate high fat adaptation, potentially due to the blunted capacity for CHO oxidation. Abstract: We investigated substrate utilisation during exercise after brief (5–6 days) adaptation to a ketogenic low‐carbohydrate (CHO), high‐fat (LCHF) diet and similar washout period. Thirteen world‐class male race walkers completed economy testing, 25 km training and a 10, 000 m race (Baseline), with high CHO availability (HCHO), repeating this (Adaptation) after 5–6 days' LCHF ( n = 7; CHO: <50 g day −1, protein: 2.2 g kg −1 day −1 ; 80% fat) or HCHO ( n = 6; CHO: 9.7 g kg −1 day −1 ; protein: 2.2 g kg −1 day −1 ) diet. An Adaptation race was undertaken after 24 h HCHO and pre‐race CHO (2 g kg −1 ) diet, identical to the Baseline race. Substantial (>200%) increases in exercise fat oxidation occurred in the LCHF Adaptation economy and 25 km tests, reaching mean rates of ∼1.43 g min −1 . However, relative V ̇ O 2 (ml min −1 kg −1 ) was higher ( P < 0.0001), by ∼8% and 5% at speeds related to 50 km and 20 km events. During Adaptation race warm‐up in the LCHF group, rates of fat and CHO oxidation at these speeds were decreased and increased, respectively ( P < 0.001), compared with the previous day, but were not restored to Baseline values. Performance changes differed between groups ( P = 0.009), with all HCHO athletes improving in the Adaptation race (5.7 (5.6)%), while 6/7 LCHF athletes were slower (2.2 (3.4)%). Substrate utilisation returned to Baseline values after 5–6 days of HCHO diet. In summary, robust changes in exercise substrate use occurred in 5–6 days of extreme changes in CHO intake. However, adaptation to a LCHF diet plus acute restoration of endogenous CHO availability failed to restore high‐intensity endurance performance, with CHO oxidation rates remaining blunted. Key points: Brief (5–6 days) adaptation to a low carbohydrate high fat diet in elite athletes increased exercise fat oxidation to rates previously observed with medium (3–4 weeks) or chronic (>12 months) adherence to this diet, with metabolic changes being washed out in a similar time frame. Increased fat utilisation during exercise was associated with a 5–8% increase in oxygen cost at speeds related to Olympic Programme races. Acute restoration of endogenous carbohydrate (CHO) availability (24 h high CHO diet, pre‐race CHO) only partially restored substrate utilisation during a race warm‐up. Fat oxidation continued to be elevated above baseline values although it was lower than achieved by 5–6 days' keto adaptation; CHO oxidation only reached 61% and 78% of values previously seen at exercise intensities related to race events. Acute restoration of CHO availability failed to overturn the impairment of high‐intensity endurance performance previously associated with low carbohydrate high fat adaptation, potentially due to the blunted capacity for CHO oxidation.